2018
DOI: 10.3390/genes9040210
|View full text |Cite
|
Sign up to set email alerts
|

Quorum Sensing and Quorum Quenching in Agrobacterium: A “Go/No Go System”?

Abstract: The pathogen Agrobacterium induces gall formation on a wide range of dicotyledonous plants. In this bacteria, most pathogenicity determinants are borne on the tumour inducing (Ti) plasmid. The conjugative transfer of this plasmid between agrobacteria is regulated by quorum sensing (QS). However, processes involved in the disturbance of QS also occur in this bacteria under the molecular form of a protein, TraM, inhibiting the sensing of the QS signals, and two lactonases BlcC (AttM) and AiiB that degrade the ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 38 publications
(24 citation statements)
references
References 73 publications
(124 reference statements)
0
24
0
Order By: Relevance
“…The actual physiological significance of AHL-degrading enzymes remains largely unclear 59 . Several authors have suggested that AHL degradation could be related with a self-regulation of intercellular systems 25 . Using different AHL biosensor strains we found that strain P6 does not produce any AHLs, nor could we identify any gene coding for a QS signal synthase (luxI) in the genome of the type strain P. segetis FR1439 T .…”
Section: Discussionmentioning
confidence: 99%
“…The actual physiological significance of AHL-degrading enzymes remains largely unclear 59 . Several authors have suggested that AHL degradation could be related with a self-regulation of intercellular systems 25 . Using different AHL biosensor strains we found that strain P6 does not produce any AHLs, nor could we identify any gene coding for a QS signal synthase (luxI) in the genome of the type strain P. segetis FR1439 T .…”
Section: Discussionmentioning
confidence: 99%
“…A. tumefaciens is a niche‐constructing pathogen that genetically modifies the plant host genome by transferring a part (the transfer DNA (T‐DNA)) of its virulence Ti plasmid (Barton et al ., ; Dessaux & Faure, ). When expressed into the plant cell nucleus, the T‐DNA genes divert the host hormonal and metabolic pathways to provoke the development of galls or plant tumors (Deeken et al ., ).…”
Section: Introductionmentioning
confidence: 99%
“…Proline was recently proposed to modulate the plant defense response to Agrobacterium tumefaciens. Proline accumulates in plant tumors, and functions as a competitive antagonist of gamma-aminobutyric (GABA)-dependent plant defense, interfering with the GABA-induced degradation of quorum-sensing signal [44][45][46]. Proline can therefore promote Agrobacterium infection and horizontal transfer of the Ti plasmid.…”
Section: Regulatory Functions Of Prolinementioning
confidence: 99%
“…Proline can therefore promote Agrobacterium infection and horizontal transfer of the Ti plasmid. The above-listed examples suggest that proline functions as versatile cellular signal in both animal and plant cells [44,45].…”
Section: Regulatory Functions Of Prolinementioning
confidence: 99%